"New" lectins for the identification of erythrocyte cryptantigens and the classification of erythrocyte polyagglutinability: Medicago disciformis and Medicago turbinata. Issue 2 (February 1983) - Bird, GWG; Wingham, June
Abstract : The seeds of Medicago disciformis and Medicago turbinata contain lectins for T or Th but not Tk or Tx red cell cryptantigens. Extracts of Medicago disciformis seeds are a useful addition to a panel of lectins used in the classification of red cell cryptantigens and of red cell polyagglutinability.